ANALISIS FAKTOR LINGKUNGAN YANG BERHUBUNGAN DENGAN PERILAKU SAFETY DRIVING PADA PENGEMUDI DUMP TRUCK - Paulo De Risky; Roza Asnel; Kursiah Warti Ningsih (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2019)
Safety driving is a good and safe driving behavior to avoid traffic problems. Such as personal safety and also the other road users. An indicipline person when driving can cause accident. Of many accidents that occured in Indonesia, most of (90.3%) was caused by human error factor. Preliminary results of a study on a driver of a dump truck PT Hutama Karya there were accident between two dump trucks there for two glass of dump trucks broke at the time of operations. The purpose of this research is to know the factors related to the behavior of the driving safety (safety driving). The type of this research is quantitative research with the analytic method uses the approach of cross sectional. The research was carried out during 1 (one) month of PT Hutama Karya. Infrastructure Section 1 with a population of 31 respondents were sampled. Research on measuring instrument is the questionnaire. The data was analyzed with univariate and bivariate by using chi square test. The results showed a relationship category of work experience (P value = 1.000 pronounced > 0.05), educational level (P value = 0.685 pronounced > 0.05), training (P value = 0, 458 pronounced > 0.05) road conditions (P value = 0.000 < pronounced 0.05) and weather conditions (P value = . 001< pronounced 0.05). The conclusion from this study is there is no relationship between the behavior of the safety driving with work experience, level of education, Training and Safety driving, while the road conditions and weather conditions there is a relationship. Then it is recommended to be carried out training of driving safety and SWA on drivers thoroughly.